(untitled) (Advances in Applied Biological Research, 2026)
Rabi pulses like chickpeas (Cicer arietinum L.), lentils (Lens culinaris Medik.), pigeonpeas (Cajanus cajan L.), and cowpeas (Vigna unguiculata L.) serve as fundamental sources of protein, iron, zinc, and dietary fiber. Nonetheless, antinutritional factors (ANFs) including phytic acid, tannins, protease inhibitors, and raffinose family oligosaccharides impede nutrient absorption. This study encapsulates the molecular mechanisms underlying protein biosynthesis, encompassing seed storage protein accumulation, nitrogen assimilation via GS/GOGAT, and essential transcriptional regulators involved in seed development. Emphasis is placed on protein bioavailability rather than mere accumulation, with a focus on strategies to mitigate ANF synthesis through genomics-assisted breeding. Advanced techniques such as CRISPR/Cas9 gene editing, quantitative trait loci (QTL) mapping, and genome-wide association studies (GWAS) have been employed to identify promising targets for reducing ANFs and bolstering nutritional content. The integration of contemporary breeding approaches with processing techniques presents a viable pathway to cultivate nutritionally enhanced and climate-resilient pulse varieties, thereby supporting global food security and nutritional health.